Forgiveness pada Remaja yang Tinggal di Panti Asuhan - Damayanti, Ria; Sandja, Stefanus Soejanto (Noetic Psychology, 2012)
AbstractÃÂ This research aimed to describe the forgiveness and the forgiveness mean of teenagers in the orphant care. The hypothetic was the forgiveness level of the teenager lower when compared with the population norm. The population in this study were boy and girl teenagers who live in the orphant house at least one year. Using the purposive random sampling methods, 87 students were selected as the participant. Data collected using forgiveness scale TRIM-18. The result was the alternative hypothetic rejected. Forgiveness level of teenagers in orphant house were higher ciompared with the standard norm. The result found that the mean of total score of forgiveness level is 57,20 which fall in high category.ÃÂ Keywords: Forgiveness, teenager, orphant careÃÂ